German law covering the public participation in planning and building infrastructure projects - Bothe, Anja (2015)
Large size infrastructure projects, such as airport, rail and road extensions, are particularly likely to encounter frequent citizens´ protests. The experience with the enhancements of the Stuttgart train station is an especially relevant example, since it has motivated the economic stakeholders, as well as the German federal and regional legislators and administrations, to rethink the project. In this case, which has become known as “Stuttgart 21”, massive resistance only materialized after the planning approval procedure. As a consequence, the "Law for broadening the public participation and for the standardization of the procedures for determining sectorial plans" was introduced in the German legislature in 2012. Among other elements in this law, public participation is now required prior to the formal opening of the procedure for planning and approval of sectorial plans, as described in Article 25, paragraph 3, of the Administrative Procedure Code. In 2013, the Association of German Engineers developed standards governing the communication and public participation in planning and building infrastructure projects. These standards are directed at project sponsors, general and specialist design contractors, project managers, executing companies and their officials. In the same year, regional governments produced binding administrative provisions to intensify public participation in the planning and licensing procedures of large infrastructure projects. These standards and administrative provisions establish several mandatory steps and procedures within the regional planning and approval processes: these mandatory steps include scoping the previous and present participation of the public and their interaction, both at formal and informal levels, conducting an official investigation to show just cause for the project, establishing internet access to the project allowing for on‐line search of the detailed plans by the public, a requirement to request and enable public participation periodically as the planning process develops, and a need to re‐ evaluate these new rules as appropriate. Similar rules have been introduced since the 1980’s by the European Union to advance and implement environmental protection. The main objective of these mandatory steps is a more efficient harmonization of the different interests involved in spatial planning. In order to establish a more solid foundation for a critical analysis of several of the elements in these rules, this paper discusses the essential factors impacting these types of plans, the skills required in their preparation, the strategies leading to acceptance of those plans, and the possible dynamics affecting their implementation. Nevertheless, these legal, administrative and private rules have come under some criticism, as listed below: ‐ several basic aspects of these rules are not sufficiently focused on the associated extra‐legal problems that they raise; ‐ some elements are voluntary rather than mandatory, while others are not precisely defined so as not to scare away potential investors; 19 ‐ while aiming at achieving more efficiency, several new obligations limit, qualitatively as well as quantitatively, the holding of successive stages of public participation, partly due to a clause that excludes the discussion of public rights which have not been presented during prior public participation; ‐ concerning environmental protection interests, the obligations of evaluation and participation focus only on the processes themselves, but do not aim at avoiding any resulting environmental harm.